COMPARISON OF STATE REVENUES PAID BY MINARAK BRANTAS GAS, Inc. BEFORE AND AFTER THE IMPLEMENTATION OF THE GROSS SPLIT (REGULATION OF THE MINISTER OF ESDM NO. 8 YEAR 2017) - Pico Putra Admiral; Dudi Rianto (Jurnal Scientia, 2023)
For the sake of facilitating the analysis process, the author uses secondary data that has been published through official quarterly and monthly reports to the state (SKKMIGAS). The results of the analysis concluded that MBGI deposits to stake holders, namely the State, since the enactment of the Minister of Energy and Mineral Resources regulation no. 8 of 2017, have had a positive impact on the state. MBGI, which is a contractor, gets the widest possible opportunity to carry out its work with minimum supervision from the state. This minimum supervision is obtained as compensation for transferring all investment risks to the contractor.